'Fate Worse than' artificial borders is the insidious African elite politics: the Somali case. Issue 3 (2nd September 2019) - Samatar, Abdi Ismail
ABSTRACT: The debate centred on the artificial nature of colonial political bounders in Africa and their enduring legacy continues. What is not directly addressed by this literature is the parallel and, even more, destructive political-economic culture left behind by colonial rule, reified by factions of the political elite in Africa, and that appears to be on the march in several parts of the continent. This paper examines the long-term consequences of political ethnicity and corruption in inducing new boundaries within the nation and that is ominously undermining the vitality and further development of civic political culture in the continent. Somalia, arguably the most culturally homogenous nation-state in the continent, provides historical evidence to sustain the argument.